2020
DOI: 10.1016/j.ijrobp.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Oncologist Perceptions of Telemedicine from Consultation to Treatment Planning: A Mixed-Methods Study

Abstract: Purpose Telemedicine was rapidly implemented for initial consultations and radiation treatment planning in the wake of the coronavirus disease 2019 (COVID-19) pandemic. In this study, we explore utilization of and physician perspectives on this approach in an attempt to identify patient populations that may benefit most from virtual care. Methods and Materials This is a mixed-methods study with a convergent design. Approximately 6 to 8 weeks after implementation of tele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 24 publications
5
78
0
Order By: Relevance
“…Clinicians had to quickly pivot to provide substantial amounts of virtual care, resulting in the need to learn new workflows. In qualitative studies examining clinician telemedicine perspectives in the pandemic’s wake, clinicians reported challenges with physical examination, workflow concerns, burnout, and reduced personal connection with patients [ 8 , 9 ]. Although these studies set a baseline for understanding clinician barriers to telemedicine, they only explored perceptions of a relatively small number of physicians [ 8 , 10 ] or were limited to physicians from one specialty [ 9 , 11 - 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians had to quickly pivot to provide substantial amounts of virtual care, resulting in the need to learn new workflows. In qualitative studies examining clinician telemedicine perspectives in the pandemic’s wake, clinicians reported challenges with physical examination, workflow concerns, burnout, and reduced personal connection with patients [ 8 , 9 ]. Although these studies set a baseline for understanding clinician barriers to telemedicine, they only explored perceptions of a relatively small number of physicians [ 8 , 10 ] or were limited to physicians from one specialty [ 9 , 11 - 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In qualitative studies examining clinician telemedicine perspectives in the pandemic’s wake, clinicians reported challenges with physical examination, workflow concerns, burnout, and reduced personal connection with patients [ 8 , 9 ]. Although these studies set a baseline for understanding clinician barriers to telemedicine, they only explored perceptions of a relatively small number of physicians [ 8 , 10 ] or were limited to physicians from one specialty [ 9 , 11 - 13 ]. Furthermore, few studies assessed clinician perspectives on effectively integrating trainees into telemedicine workflows, an important area to address to support the clinical learning environment.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Because of the pandemic, telemedicine has seen exponential growth and widespread adoption, 4 consisting of more than 90% of visits in some clinics. 5,6 Telemedicine has been used in almost every specialty, including procedural specialties. 5,[7][8][9][10][11][12][13][14][15][16][17] Further, especially since the beginning of the COVID-19 pandemic, telemedicine use has increased internationally.…”
mentioning
confidence: 99%
“…Different studies delved into physicians’ perceptions toward telemedicine, one of which showed that ER physicians were the least likely to prefer telemedicine [ 14 ], while 96% of radiation oncologists foresee telemedicine to have a role beyond the pandemic [ 15 ]. Furthermore, 80% of ophthalmology patients preferred to have telemedicine as an option for first-visit evaluation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%